Jaufre Rudel: Longinquus amor, amor de lonh, amors loingtaignes. Dallo spazio al tempo? (Carte Romanze, 2023)
Abstract: The essay is focused on the famous formula amor de lonh in Jaufre Rudel's Lanquan li jorn son lonc en mai. The metric structure appears to be built around the mot-refrain lonh and the syntagm amor de lonh first with variatio and then with anaphora (in coblas I-V and VI-VII respectively). According to this data and textual references as Propertius' longinquus amor – already considered by Roncaglia and Patrizia Onesta as a literary topos in Jaufre's lyric – and Lai d'Aristote's amors loingtaignes, the famous syntagm amor de lonh (later fixed and of incomparable literary success) was probably used by the author in the temporal meaning of "constant, long-lasting love".